1993
DOI: 10.1161/01.res.72.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of angiotensin II receptors on ventricular myocytes after myocardial infarction in rats.

Abstract: To determine the effects of acute myocardial infarction on the regulation of angiotensin II (Ang II) receptors and contractile performance of left and right ventricular myocytes, coronary artery ligation was surgically induced in rats, and Ang II receptor density and affinity and the mechanical properties of surviving muscle cells were examined 1 week later. Physiological determinations of cardiac pump function revealed the presence of ventricular failure, which was associated at the cellular level with a depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 50 publications
(22 reference statements)
5
61
2
3
Order By: Relevance
“…Thus, the number of AT1 receptors defines the biological efficacy of angiotensin II. The RAS has also been implicated in cardiovascular pathology, and the upregulation of AT1 receptors in the cardiovascular system has been reported in diseases like thyroid dysfunction, hypertension and myocardial infarction [22][23][24]. Our present findings demonstrate increased densities of the AT1 receptor mRNA and protein in human atrial myocardium of patients suffering from type 2 diabetes.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, the number of AT1 receptors defines the biological efficacy of angiotensin II. The RAS has also been implicated in cardiovascular pathology, and the upregulation of AT1 receptors in the cardiovascular system has been reported in diseases like thyroid dysfunction, hypertension and myocardial infarction [22][23][24]. Our present findings demonstrate increased densities of the AT1 receptor mRNA and protein in human atrial myocardium of patients suffering from type 2 diabetes.…”
Section: Discussionsupporting
confidence: 71%
“…[45][46][47][48] Microscopic analysis revealed that cross-sectional areas of cardiac myocytes were increased both in KO mice and in WT mice (Fig 6A), indicating that each cardiac myocyte was increased in size by pressure overload without AT 1 signaling. Perivascular fibrosis was prominent after pressure overload in KO hearts as well as in WT hearts (Fig 6B).…”
Section: Histological Changes In Hypertrophied Heartsmentioning
confidence: 98%
“…AT 2 receptors are numerous in neonatal cardiac myocytes, but their number decreases rapidly postnatally and adult ventricular myocytes have been claimed to possess exclusively AT 1 . 40,41 The possibility was raised that AT 2 is re-expressed in the overloaded heart in both myocytes 42 and fibroblasts, 43 but the myocyte localization remained unclear. In this study, AT 2 was detected in nonstretched myocytes and its expression increased with the mechanical stimulus.…”
Section: Adp53m and Myocyte Rasmentioning
confidence: 99%